Phospho-mTOR (Ser2481) colocalizes with condensed chromosomes during metaphase - Kosach, V.R.; Tykhonkova, I.O.; Cherednyk, O.V.; Filonenko, V.V.; Khoruzhenko, A.I. (Вiopolymers and Cell, 2016)
Aim. To study the subcellular localization of phospho-mTOR (Ser2481) in cultured cells of human cancer cell lines. Methods. Immunofluorescent analysis of phospho-mTOR (Ser2481) subcellular localization in cultured MCF-7 (human breast adenocarcinoma) and HepG2 (human liver carcinoma) cells. Results. For the first time phospho-mTOR (Ser2481) was detected as bright spots situated in the equatorial region of chromosomes and colocalized with condensed chromosomes during metaphase. Conclusions. In this study, we describe for the first time the co-localization of phospho-mTOR (Ser2481) and chromosomes of the metaphase plate in the MCF-7 and HepG2 cells. Our data support the hypothesis that phospho-mTOR (Ser2481) could act as a CPP (chromosomal passenger protein)-like kinase, which takes part in the regulation of mitosis progression.